Control of the dual emission behaviour of μ-oxo-bridged Si(iv) corrole dimers by substituent bulkiness. (11th July 2022) - Yamagata, Kyo; Ueta, Kento; Nakai, Akito; Osuka, Atsuhiro; Tanaka, Takayuki
Abstract : μ-Oxo-bridged Si(iv ) corrole dimers show dual emission behavior. Their conformational relaxation can be controlled by substituent bulkiness. Abstract : The μ-oxo-bridged dimer of Si(iv ) corrole has been recently reported to exhibit dual emissive properties depending on the solvent viscosity. Here we examined the control of the excited-state dynamics and dual emission by meso -aryl substituents. Less hindered 10-unsubstituted and 10-phenyl-5, 15-bis(pentafluorophenyl)-Si(iv ) corrole dimers and the more hindered 5, 15-bis(pentafluorophenyl)-10-(2, 4, 6-trimethoxy)phenyl-Si(iv ) corrole dimer were newly prepared and characterised. Interestingly, their solid-state structures are different: parallel, anti-parallel or orthogonal. In contrast, the energy-minimized structures in the excited state have been suggested to be parallel in all cases owing to the significant excimer-like stabilization. As a result, different emission behaviours and viscosity dependence were observed.